2009
DOI: 10.1124/mol.109.056309
|View full text |Cite
|
Sign up to set email alerts
|

BCL-2 Family Inhibitors Enhance Histone Deacetylase Inhibitor and Sorafenib Lethality via Autophagy and Overcome Blockade of the Extrinsic Pathway to Facilitate Killing

Abstract: We examined whether the multikinase inhibitor sorafenib and histone deacetylase inhibitors (HDACI) interact to kill pancreatic carcinoma cells and determined the impact of inhibiting BCL-2 family function on sorafenib and HDACI lethality. The lethality of sorafenib was enhanced in pancreatic tumor cells in a synergistic fashion by pharmacologically achievable concentrations of the HDACIs vorinostat or sodium valproate. Overexpression of cellular FLICE-like inhibitory protein (c-FLIP-s) or knockdown of CD95 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 55 publications
2
64
1
Order By: Relevance
“…4D). 29,30 In addition to MEK1/2 inhibitors, we have also observed in other tumor types that inhibitors of SRC family kinases interact with CHK1 inhibitors to kill tumor cells.…”
Section: Resultsmentioning
confidence: 94%
“…4D). 29,30 In addition to MEK1/2 inhibitors, we have also observed in other tumor types that inhibitors of SRC family kinases interact with CHK1 inhibitors to kill tumor cells.…”
Section: Resultsmentioning
confidence: 94%
“…13,14 Recent findings have also revealed that sorafenib generated a protective form of autophagy in gastrointestinal and pancreatic tumor cells. 15,16 However, both how these therapies induce autophagy and whether such autophagy contributes to tumor cell death or is a mechanism of resistance remains uncertain and varies depending on the cell type and stimulus. 17 In the present study, we found that direct stimulation of ER stress by sorafenib in HCC induced autophagy via upregulation of the IRE1 pathway and that inhibition of autophagy promoted ER stress-related apoptosis of HCC cells in vivo and in vitro.…”
Section: Targeting Autophagy Enhances Sorafenib Lethality For Hepatocmentioning
confidence: 99%
“…A total of 10,000 to 25,000 stained cells per sample were acquired and analyzed in a FACScan or FACSCalibur flow cytometer by using CellQuest and Paint-A-Gate softwares (Becton Dickinson). Lethal dose 50 (LD 50 ) was defined as the concentration of drug required to reduce cell viability by 50%. For drug combinations, combination indexes (CI) were calculated with the CalcuSyn software version 2.0 (Biosoft) by using the Chou and Talalay algorithm.…”
Section: Translational Relevancementioning
confidence: 99%